2022
DOI: 10.1111/ics.12765
|View full text |Cite
|
Sign up to set email alerts
|

Changes in levels of omega‐O‐acylceramides and related processing enzymes of sun‐exposed and sun‐protected facial stratum corneum in differently pigmented ethnic groups

Abstract: Introduction:We report on the differences in ceramide composition and levels of omega-O-acylceramide processing enzymes of sun-exposed and sun-protected facialstratum corneum (SC) among Albino African, Black African and Caucasian women living in South Africa.Methods: Tape strippings were taken from the sun-exposed cheek and the sunprotected postauricular site (PA). In two subsets proteomic (n = 18) and lipidomic (n = 24) analysis were performed using mass-spectrometry-based shotgun platforms.Results: No signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
(112 reference statements)
1
9
0
Order By: Relevance
“…As shown in Figure 24, for our studies, there are no differences in the 12 ceramide classes we measured on cheek SC for Black African and Caucasian females living in South Africa. However, the acylceramides we measured are elevated in skin of Albino Africans (EOS, EODS, EOH and EOP) [86]. We propose these increases are related to reductions in the corneocyte ceramide processing enzymes previously described such as reductions in 12R-LOX activity but in this study, we also demonstrated reductions in the mass levels of SDR9C7 by mass spectrometry-based proteomics in the Albino Africans.…”
Section: Eop] [Nds] [Nh] [Np]supporting
confidence: 65%
“…As shown in Figure 24, for our studies, there are no differences in the 12 ceramide classes we measured on cheek SC for Black African and Caucasian females living in South Africa. However, the acylceramides we measured are elevated in skin of Albino Africans (EOS, EODS, EOH and EOP) [86]. We propose these increases are related to reductions in the corneocyte ceramide processing enzymes previously described such as reductions in 12R-LOX activity but in this study, we also demonstrated reductions in the mass levels of SDR9C7 by mass spectrometry-based proteomics in the Albino Africans.…”
Section: Eop] [Nds] [Nh] [Np]supporting
confidence: 65%
“…Preliminary research also indicates that the SC is more depleted of natural moisturizing factors in the cheek areas [ 46 ]. Compared with other non‐photodamaged sites, corneocyte envelopes are also more immature on the cheeks which relates to reduced 12R‐lipoxygenase (12R‐LOX), epidermis‐type lipoxygenase 3 (eLOX3) and transglutaminase‐1 levels and activities together with reduced ceramide EOS levels [ 47 , 48 , 49 , 50 , 51 ]. Nevertheless, more studies are needed to decipher the biological and anatomical differences on the different facial locations in order to explain the relative differences in the hydration maps between the two instruments.…”
Section: Discussionmentioning
confidence: 99%
“…ultraviolet radiation (UVR), ozone], ageing and inflammatory disease (e.g. atopic dermatitis, psoriasis, xerosis, ichthyosis) [14–17]. Studies into the barrier function and stratum corneum lipid composition of ethnic or pigmented skin are so far inconclusive, with more work needed to identify any potential differences [18,19].…”
Section: Lipids Have Different Roles Throughout the Skinmentioning
confidence: 99%
“…ultraviolet radiation (UVR), ozone], ageing and inflammatory disease (e.g. atopic dermatitis, psoriasis, xerosis, ichthyosis) [14][15][16][17]. Studies into the barrier function and stratum corneum lipid composition of ethnic or pigmented skin are so far inconclusive, with more work needed to identify any potential differences [18,19] Sphingomyelin, a sphingolipid providing ceramides via a hydrolysis pathway, can also contribute to the maintenance of the skin barrier via phosphorylation of the signal transducer and activator of transcription 3 (STAT3) [29].…”
Section: Key Pointsmentioning
confidence: 99%